Optimization Experimental Procedure and Setup of a Guided Inquiry Laboratory Worksheet of Transesterification Reaction on Biodiesel Production - Dwiyanti, Gebi; Suryatna, Asep; Nurhayati, Mita (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2018)
The aims of this research are producing an optimal experiment procedure and determining the feasibility of a guided inquiry laboratory worksheet of transesterification reaction on biodiesel production context. This research used research and development methods that composed of two stages, initial product preparation and model development (until limited testing). The data sources of this research are 20 students grade XII of science, seven chemistry teachers and three lecturers from chemistry education program of FPMIPA UPI. The instruments that used in this research are optimization and observation sheets of inquiry stages implementation, rubric of assessment students’ answer, sheets of assessment by teacher and lecturer, and student’s response questionnaires. The optimization of biodiesel production is: 12 mL of palm oil is added into erlenmeyer flask that contained boiling stone, then added by 0.12 g Potasium hidroxide in 4.5 mL methanol solution. The erlenmeyer flask then closed by rubber stopper with test tube in the middle of rubber stopper that filled with water and heated at 45oC in water bath for 5 mins by shaking the flask. The feasibility of laboratory experiment is categorized as very good. Teacher and lecturer assessment on the concept conformity, language, and the appearance of worksheet is categorized as very good. Student’s responses of laboratory activity and the worksheet are good.